Neurofibromatosis type‐1‐associated diffuse lung disease in children. Issue 11 (13th August 2019) - Spinnato, Paolo; Facchini, Giancarlo; Tetta, Cecilia; Lotrecchiano, Ludovica; Colangeli, Marco; Bazzocchi, Alberto; Albisinni, Ugo; Cutrera, Renato; Tomà, Paolo; Bartoloni, Alessandra
Abstract: Objective: The purpose of the study was to investigate the occurrence of diffuse lung disease associated with neurofibromatosis type‐1 in the pediatric population. We also aimed at evaluating computed tomography (CT) findings of the disease. Introduction: Diffuse lung disease associated with neurofibromatosis type‐1 has been described mainly in the adult population; causes and connections between lung disease and the genetic disorder are still not completely understood. The occurrence of the disease in non‐smokers, the presence of blebs, bullae or cysts distinct from smoking‐related emphysema on CT and the histopathological pattern characterized by lymphoplasmocytic inflammation and fibrosis, are all factors that support the association of diffuse lung disease as a distinct manifestation of neurofibromatosis. Methods: We retrospectively reviewed, with "lung window, " all the spinal CTs performed in two institutions from 2004 to 2018 for scoliosis assessment in pediatric patients affected by neurofibromatosis type‐1 (group 1). Moreover, we retrospectively analyzed a control group of pediatric patients, affected by severe scoliosis without neurofibromatosis (group 2). Differences between the two groups were analyzed to ascertain whether the disease can be related to neurofibromatosis type‐1 rather than to scoliosis. Results: Six out of thirty one subjects from group 1 (19.4%) showed a condition of diffuse lung disease while none (0 of 31) in group 2. The differences between the two groups were statistically significant ( P  = .01). All six patients showed subpleural blebs, bullae, or cysts without basilar fibrosis. Conclusion: Our research consolidates the hypothesis that diffuse lung disease is a direct manifestation of neurofibromatosis type‐1 and that early onset is possible, even in pediatric patients.